2022
DOI: 10.3390/f13020277
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Rescues Native Trees in the Biodiversity Hotspot of Mauritius

Abstract: Many tropical invasive species have allelopathic effects that contribute to their success in native plant communities. Pyrolyzed biomass (“biochar”) can sorb toxic compounds, including allelochemicals produced by invasive plants, potentially reducing their inhibitory effects on native species. Strawberry guava (Psidium cattleianum) is among the most important allelopathic invasive species on tropical islands and recognized as the most serious threat among invasive species in the global biodiversity hotspot of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…BCs have the capacity to sorb or immobilize toxic metals (Beesley et al, 2011; Rees et al, 2014), salts (Hammer et al, 2015; Thomas et al, 2013), and toxic organic compounds (Hale et al, 2015), including allelochemicals (Elmer & Pignatello, 2011; Gámiz et al, 2021). Allelopathy increases the negative effects of many invasive species and makes them more difficult to manage, but BC is a promising tool against allelopathic invasive species (Sujeeun & Thomas, 2022) due to its ability to sorb and reduce the bioavailability of a wide range of organic compounds (Hall et al, 2014; Kumar et al, 2020). Recent laboratory trials have shown that BCs have the potential to alleviate the inhibitory effects of a wide range of allelopathic invasive plants (Bieser et al, 2022; Shen et al, 2020; Sujeeun & Thomas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…BCs have the capacity to sorb or immobilize toxic metals (Beesley et al, 2011; Rees et al, 2014), salts (Hammer et al, 2015; Thomas et al, 2013), and toxic organic compounds (Hale et al, 2015), including allelochemicals (Elmer & Pignatello, 2011; Gámiz et al, 2021). Allelopathy increases the negative effects of many invasive species and makes them more difficult to manage, but BC is a promising tool against allelopathic invasive species (Sujeeun & Thomas, 2022) due to its ability to sorb and reduce the bioavailability of a wide range of organic compounds (Hall et al, 2014; Kumar et al, 2020). Recent laboratory trials have shown that BCs have the potential to alleviate the inhibitory effects of a wide range of allelopathic invasive plants (Bieser et al, 2022; Shen et al, 2020; Sujeeun & Thomas, 2017).…”
Section: Introductionmentioning
confidence: 99%